228 Relationship between biomarkers of stress, inflammation and pain, and lameness in feedlot cattle. (7th December 2018) - Marti, S; Janzen, E; Pajor, E; Orsel, K; Jelinski, M; Dorin, C; Thomson, D; Coetzee, J; Shearer, J; Millman, S; Schwartzkopf-Genswein, K
Abstract: Over a two-year period, 1207 lame (L) feedlot cattle with gait scores > 1 (based on a 4-point scale with 1 = mildly lame and 4 =severely lame)) were identified by feedlot personnel for the first time, and an additional 98 non-lame cattle (NL) (gait score = 0) from the same pen as the lame cattle, were used to evaluate the relationship between specific biomarkers of stress, inflammation and pain and lameness severity. All L and NL cattle were sampled immediately prior to being evaluated in a squeeze chute. Biomarkers assessed included salivary cortisol (SC), hair cortisol (HC), rectal temperature (RT), haptoglobin, serum amyloid-A (SAA), substance P (SP) and complete blood cell count (red blood cells (RBC), hematocrit, platelet count and white blood cells (WBC)). Data was analyzed using a mixed-effects model with lameness the fixed effect and season as the random effect. No differences ( P > 0.10) were observed in SC, HC, RT, RBC and hematocrit. Haptoglobin and SAA were greater ( P < 0.001) in L (1.67 ± 0.128 g/L and 188 ± 11.3 g/L, respectively) than NL (0.62 ± 0.128 g/L and 102 ± 11.3 g/L, respectively) cattle as well as platelet count ( P < 0.01), hemoglobin ( P < 0.001) and WBC ( P < 0.001). SP tended to be greater( P = 0.08) in L (63.0 ± 2.10 pg/mL) than NL (57.1 ± 2.10 pg/mL) cattle. Biomarkers of stress as SC and HC, and RT were not able to discriminate between lame and non-lame cattle. However, haptoglobin, SAA and WBC were useful indicators of lameness in feedlot cattle. These biomarkers could be used in future studies evaluating lameness mitigation strategies.